Analysis of Phonological Errors in SD N 1 Jojo on The Theme of Heroes - Kiswanti; Syarifah Nur Aulia; Mefiani, Sandrina; Rani Setiawaty (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe errors in language use, especially in the area of phonology, in students' essays at SD N 1 Jojo. The method used in this research is qualitative narrative. The data comes from a narrative essay entitled